Comunicación y desinformación en elecciones: tendencias de investigación en España y Portugal = Communication and disinformation in elections: research trends in Spain and Portugal - Rivas-de-Roca, Rubén (2022)
The relationship between politics and communication is not new, but it seems to have sparked renewed academic interest in recent years. The transformations that have affected contemporary democratic societies, such as digital technologies or the rise of disinformation, explain the concern about these issues. One of the topics of greatest interest are the elections, as the moment in which participatory democracy takes place. In this changing context, this study aims to carry out a review of the main research on political communication and elections in the Iberian area (Spain and Portugal), identifying possible similarities and divergences. The objective is to know the research trends (topics and methods) in order to later pose pending challenges. An in-depth bibliographic review was conducted published during 2008-2021 in WoS, Scopus and reference books. As results, similarities are observed in the methodological preference for content analysis, although the topics addressed differ depending on national circumstances, beyond a certain coincidence in the analysis of national legislative elections. In Spain, the action of the new parties on social networks has been especially addressed, while in Portugal the interest in television prevails. Likewise, the breakthrough of scientific production in Spain contrasts with the lower number of studies in the Portuguese cases. Researchers from both countries face the challenge of offering comparative studies between elections, as well as implementing a higher methodological plurality that allows to delve into the reasons of communicative actions.